The making of Indian secularism empire, law and Christianity, 1830-1960 - Chatterjee, Nandini 1976- (Cambridge imperial and post-colonial studies series., 2011)
"This book examines religion in India under British rule and the immediate postcolonial years, from an unusual angle, placing Indian Christians at the centre of the story. It addresses legal developments regarding religion and its practice during British imperial rule in India, and the political emergence of Indian Christians as a community in this context"--Provided by publisher.